AN APPLICATION OF VIDEO SCREENCAST FEEDBACK ON WRITING ASSIGNMENTS: A CASE STUDY (Journal of Foreign Language Studies, 2024)
Most research on screencast feedback has focused on student’s writing progress without scrutinizing the attitude of students towards this type of feedback, especially in the context of developing countries. This research was carried out to explore the perspectives of Vietnamese foreign language students on screencast feedback in their writing practices. Participants were two B1 level (Common European Framework of Reference for languages - CEFR) students who had studied academic writing for a year during which they had only received oral and written feedback. In this study, a three-month experiment was performed to provide video-based feedback to ensure the participants had enough time to experience this new type of feedback. Afterwards, two indepth interviews were conducted. The results revealed that both students expressed their favorable attitude to screencast feedback, especially in the aspects of convenience, clarity, learning engagement and motivation stimuli. However, they also showed concern about some issues relating to technology and interaction.
Keywords: feedback; screen-casting; video; multimedia; writing skills